PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - S.B, Siti Masitah (STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
The contextual approach is a teaching style that links the curriculum to real-world applications. One of the obstacles faced by students is the difficulty in distinguishing units of time. Therefore, this research utilizes a contextual approach. This research uses Classroom Action Research (CAR) with 38 second-grade students from SD Al-Washliyah No. 83 Gunting Saga, North Labuhanbatu as subjects. The implementation of contextual learning strategies has proven beneficial in improving mathematics learning outcomes, particularly in the material of recognizing time. This is evidenced by the percentage of students' learning outcomes during the pre-cycle where only 11 students completed (28.94%) and 27 students were still not finished (71.60%). In the first cycle of implementing contextual learning, there was an increase in student learning outcomes, with 26 students (68.42%) categorized as completed and 12 students (31.58%) categorized as incomplete. Meanwhile, in the second cycle of implementing contextual learning, the number of students who completed increased to 34 students (89.47%) with 4 students still incomplete (10.53%). Thus, the contextual learning strategy has been proven to significantly improve student learning outcomes. This study also found that through contextual learning, students were more engaged in the learning process and could apply the material to real-life situations.